Air Handling Unit with Heat Pump. (June 2019) - Kny, M; Mazanec, V; Adamovský, D; Včelák, J
Abstract: The paper focuses on the design, implementation and measurement of parameters of an air handling unit (AHU) with the Peltier cells. This is a small local modular AHU for fresh air flows of 50 to 200 m 3 /hr. The unit is designed for ventilation of residential and administrative buildings. Computer simulations were utilized designing the unit (including CFD), and many measurements were performed. The design of the AHU uses the Peltier effect, which transfers the heat from the exhaust air drawn from the room to the fresh supply air (heating mode). In reverse, the unit then allows for pre-cooling of the supply air (cooling mode). The air handling unit with the Peltier element does not achieve the high efficiency of the compressor cycle units, but is much simpler and has longer life expectancy.